Integrated analogue–digital control circuit for photonic switch matrices. Issue 12 (1st June 2016) - Enne, R.; Hofbauer, M.; Zecevic, N.; Goll, B.; Zimmermann, H.
Abstract : An analogue–digital circuit for thermal control of the resonance frequency of optical ring resonators is suggested. This approach is characterised by a low power dissipation of 209 µW and needs only 2800 µm 2 of chip area in 0.16 µm CMOS technology. Therefore, it is well appropriate to be used to control each of the cells of large optical switch matrices. Compared with a purely analogue heater control approach the power dissipation is reduced to 7%.